A new species of the genus Phytoecia Dejean 1835 (Coleoptera: Cerambycidae) from Eastern Turkey - D.G. Kasatkin (Кавказский энтомологический бюллетень, 2010)
Phytoecia (s. str.) shokhini sp. n., a new species is described from Tunceli province (Eastern Turkey)